The Influence of Parent-Adolescent Conflict on Adolescent Academic Retention in the South Dayi District in the Volta Region, Ghana - Amedi, Wisdom; Pufaa, Felicia Esinam (European Scientific Journal, ESJ, 2025)
Parent-adolescent conflict is a global problem that confronts most families. It remains a key concern due to its consequences on emotional, social, and psychological well-being, as well as its long-term implications for the family and the adolescents’ overall development. The purpose of this study was to explore the influence of parent-adolescent conflict on adolescents’ academic performance. The study adopted a qualitative approach and case study design. Thirty-two (32) participants were purposively selected from two Senior High Schools in the South Dayi District, and the data were thematically analyzed. Findings showed that poverty, neglect of parental obligations, broken homes, and single parenting were the leading causes of conflict between parents and adolescents. It was also revealed that parent-adolescent conflict resulted in school drop-out, lack of concentration in school, and early relationship with the opposite sex, among others. It was concluded that the adolescent stage is delicate; therefore, effective interventions and strategies must be initiated by the government in collaboration with district authorities and Non-Governmental Organizations (NGOs), to enable educators, parents, and school counsellors to help adolescents who may be experiencing academic difficulties as a result of conflict at home. It was recommended that schools should develop comprehensive counselling services, including frequent counselling sessions, to help students facing adolescent-parent conflict focus on their academic work and manage their time properly.